Linking integrative taxonomy and ecology: Diversity and population structure of two platyhelminth parasites (Digenea: Lepidapedidae) of sympatric deep-sea fishes in the Western Mediterranean. (February 2023) - Pérez-del-Olmo, Ana; Georgieva, Simona; Dallarés, Sara; Constenla, Maria; Kostadinova, Aneta; Carrassón, Maite
Abstract: Current knowledge about deep-sea parasites is limited and the data shedding light on population differentiation at host, geographical or bathymetric scales are scarce. Here, we applied an integrative taxonomic approach to the identification of metazoan parasites in a large sample of deep-sea fish species from the Western Mediterranean and assessed the diversity of Lepidapedon spp. (Digenea) and the patterns of genetic and epidemiological variation of parasite populations in relation to host, geographical and bathymetric provenance. Fully censused infrapopulations of Lepidapedon spp. were analysed from five species of deep-sea fish ( Coelorinchus mediterraneus (Mediterranean grenadier), Lepidion lepidion (Mediterranean codling), Phycis blennoides (greater forkbeard), Trachyrincus scabrus (roughsnout grenadier) and Mora moro (common mora)) collected by bottom trawling at depths of 400–2000 m. Partial fragments of the mitochondrial nad 1 gene amplified for representative samples per morphotype were used to aid species delineation. After completion of the combined morphological and molecular characterisation of select samples, the total collected material was re-identified based on a suite of differentiating morphological features. Analyses revealed low species diversity and host specificity of Lepidapedon spp. Two species infecting multiple hosts were identified: Lepidapedon desclersae and L. guevarai. Genetic analyses showed lack of genetic differentiation for populations of the more abundantly sequenced species, whereas ecological analyses depicted significant differences in epidemiological parameters of both digenean species associated with host species, geographical area and bathymetric range. Overall, our results indicate that combining population genetics with ecological analyses holds a promise of gaining insights into the factors and possible mechanisms that determine the patterns of connectivity among parasite populations in the deep sea. Graphical abstract: Image 1 Highlights: Application of an integrative taxonomic approach to fully censused parasite infrapopulations in deep-sea fishes. Novel data on the species and genetic diversity of Lepidapedon spp. in the Western Mediterranean. Low species diversity and host-specificity of Lepidapedon spp. in the area of study. Significant differences in epidemiological parameters of parasite populations in relation to their provenance.